Towards a substantive knowledge that promotes the dignity of the human being - Ginés Marco Perles; Alfredo Esteve (Journal of Innovation & Knowledge (JIK), 2017)
Today's Western individual can be described as a satisfied citizen. But while it is clear that the lives of the inhabitants of the First World are filled with a sense of satisfaction, the question immediately arises as to what this sensation is based on, if it is more than a merely skin-deep satisfaction. With reference to the recent past, human (cultural) progress tends to be quantified in three broad areas: science, morality and art, all preferably seen through a rationalist prism. Unamuno underscored the difficulty of approaching culture in these terms, with the understanding that this neglected aspects intimately linked with the life processes of "flesh and blood" individuals, processes that made it possible to achieve a sense of life that would otherwise be inaccessible. Regarding this failure to take such life processes into account, and given its propensity for generalization, science stood out among these spheres as placing an excessive weight on positivist values that by their very nature disregarded anything that could not be classified as such. This approach was in stark contrast with the open tradition upheld by Miguel de Unamuno that would be eagerly taken up by Spanish philosophy in the twentieth century. From the perspective of that philosophy it is, therefore, worth asking whether all of those aspects and elements (not only those that form part of any given human life but also those belonging to the other two main spheres of culture - art and morality - displaced by scientism because they were not positive or verifiable through experiment, because they did not lend themselves to being understood using a rationalist or logical/scientific reasoning) were not also human. Was their rejection justified?
Keywords: Y90; 650; Knowledge; Philosophy; Moral; Dignity; Humanity; Satisfaction; Rationalism; Postmodernity